Emerging economies and multinational enterprises - Tihanyi, Laszlo (College teacher) (Bingley, U.K. : Emerald, 2015)
Volume 28 of the Advances in international management focuses on the opportunities and challenges for multinational enterprises that consider emerging economies as their destinations or their homes. Chapters in this volume examine the rise of home-grown multinational enterprises in emerging economies and the challenges they face when they enter developed markets. They also analyze the co-evolution of and the dynamic interaction between market institutions and business organizations in emerging economies. The volume provides a forum for thought-provoking ideas, empirical research, and discussions, and is ideal for researchers and doctoral students whose work touches emerging markets.
Determinants of board roles in IJVs in China : control and collaboration / Xuanli Xie, Jeffrey J. Reuer, Elko Klijn -- Sources of competitiveness and multinationality : emerging market firms in the electronics industry / Sumon Kumar Bhaumik, Nigel Driffield, Ying Zhou -- Corruption and foreign direct investment : a study of Guatemala / Jose<U+0301> Godinez, Mauricio Garita -- An integrated model of upgrading and catch-up by emerging economy firms / Murali D.R. Chari -- Framing international operations management : contributions from emerging country multinationals / Afonso Fleury ... [et al.] -- Business group effects on the innovation-internationalization relationship : evidence from the Indian pharmaceutical sector / Saptarshi Purkayastha, Tatiana S. Manolova, Linda F. Edelman -- What do we know about state-owned emerging-economy firms, and how? Evaluating literature about inward and outward multinational activities / Xavier Martin, Cha Li -- Why do the Turkish firms invest in mainland Europe? / Sathyajit R. Gubbi, Sinan A. Sular -- Foreign entry mode choices of emerging market multinationals : the role of institutional voids in shaping strategic cognition / Michael Hilb -- Is springboard FDI strategy effective? Evidence from Turkish acquisitions / Victor Z. Chen, Sedat Aybar.
Print version record
Keywords: Business & Economics -- International -- General; International business; International business enterprises -- Developing countries